Prediction of hypertensive disease in pregnancy using pulse pressure waveform analysis. (18th April 2012) - Hogan, JL; O'Dwyer, V; O'Reilly, A; Farah, N; Kennelly, MM; Turner, MJ; Stuart, B
Abstract : Prediction of hypertensive disease in pregnancy remains a challenge in modern obstetrics. Risk factor based screening, ultrasound and serum markers have been used with varying success. As pre-eclampsia would appear to occur due to changes in the vasculature, the vessel wall has been investigated as a predictor of hypertension in pregnancy. This study looked at pulse pressure wave analysis, using the diastolic portion of the cardiac cycle, in the prediction of hypertensive disease of pregnancy. Women were recruited from the antenatal clinic. Women with known cardiac disease were excluded. All women had pulse pressure waveform analysis performed in the first half of pregnancy. The primary outcome studied was the development of hypertensive disease of pregnancy. Pulse wave analysis was performed on 600 patients. The elasticity of the arterial vessel wall differed in hypertensive pregnancies and in particular in pregnancies subsequently complicated by pre-eclampsia. In early pregnancy, the mean arterial pressure (p=0.02), large artery elasticity (p=0.01), small artery elasticity (p=0.02) and systemic vascular resistance (p=0.02) were all significantly different in women who later developed pre-eclampsia compared to normal pregnancy. In pregnancies complicated by pregnancy induced hypertension, mean arterial pressure measurements were significantly different in early pregnancy but arterial elasticity did not differ. Pulse pressure waveform analysis may be a useful screening tool in the prediction of hypertensive disease and in particular, pre-eclampsia. Use of this technology in combination with other screening tools may aid in the selection of high risk pregnancy for more intensive antenatal care.